2013
DOI: 10.1371/journal.pone.0081286
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphatases Decrease Their Activity during Capacitation: A New Requirement for This Event

Abstract: There are few reports on the role of protein phosphatases during capacitation. Here, we report on the role of PP2B, PP1, and PP2A during human sperm capacitation. Motile sperm were resuspended in non-capacitating medium (NCM, Tyrode's medium, albumin- and bicarbonate-free) or in reconstituted medium (RCM, NCM plus 2.6% albumin/25 mM bicarbonate). The presence of the phosphatases was evaluated by western blotting and the subcellular localization by indirect immunofluorescence. The function of these phosphatases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 58 publications
1
41
0
1
Order By: Relevance
“…Serine/threonine protein phosphatases are involved in the regulation of various sperm functions, including progressive motility (Goto and Harayama, ; Krapf et al, ), capacitation (Visconti et al, ; Signorelli et al, ), and hyperactivation (Suzuki et al, ). In this study, calyculin A‐sensitive protein phosphatases suppressed serine/threonine phosphorylation of AGC‐kinase substrates in the connecting piece, leading to protein tyrosine phosphorylation and full‐type hyperactivation in ejaculated bull spermatozoa.…”
Section: Resultsmentioning
confidence: 99%
“…Serine/threonine protein phosphatases are involved in the regulation of various sperm functions, including progressive motility (Goto and Harayama, ; Krapf et al, ), capacitation (Visconti et al, ; Signorelli et al, ), and hyperactivation (Suzuki et al, ). In this study, calyculin A‐sensitive protein phosphatases suppressed serine/threonine phosphorylation of AGC‐kinase substrates in the connecting piece, leading to protein tyrosine phosphorylation and full‐type hyperactivation in ejaculated bull spermatozoa.…”
Section: Resultsmentioning
confidence: 99%
“…; Signorelli et al. ). Previous reports have shown that the high protein phosphatase activity is correlated with low sperm motility, whereas low catalytic activity is associated with vigorous motility in bovine and monkey spermatozoa (Smith et al.…”
Section: Introductionmentioning
confidence: 97%
“…; Signorelli et al. ). It has been reported that Ser/Thr phosphatase inhibitors induce capacitation signalling (Goto and Harayama ; Krapf et al.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Protein Phosphatase activity is decreased during capacitation; this has significance because they may dephosphorylate and thus deactivate proteins required for capacitation (Signorelli et al. ). Multidrug resistance‐associated protein 4 (MRP4) is localized in the mid‐piece of bovine spermatozoa (Osycka–Salut et al.…”
Section: Signalling Pathwaysmentioning
confidence: 99%